DYNAMICS OF COMMUNITY OF LEARNING (CoL) DISCOURSE ON EMPLOYING STEM ACTIVITY IN CONDUCTING RESEARCH PROJECT - Aron, Annallee Q. (PEOPLE: International Journal of Social Sciences, 2020)
In 1995, Science Education Institute (SEI) has made the biggest revolution ever in the history of Philippine Education by guiding the Department of Education Culture and Sports (DECS) to mold young citizens who are scientifically and technologically inclined into the greatest manpower that will provide social and economic growth in the country. Part of this revolution is offering special science class with a curriculum packed with more science, mathematics, and scientific research as subjects compared to the basic education curriculum. This curriculum has been implemented in 2 decades and yet in the latest Department of Science and Technology, DOST survey in a rating of 1-7 experts gave Philippines an average score of 3.72 in terms of our global competitiveness in the world of scientific research and technology. There is the need to further revolutionized and explore not only the curriculum but also the approach of teaching scientific research especially for young scientist enthusiasts who wants to develop the skills in conducting Science Research. This study is conducted to capture the dynamics of the online discourse by analyzing the question & interaction pattern and response among the CoL (with the presence of the more-knowledgeable-others) using the Online google classroom STEM lesson version on developing a quality research investigatory projects and in changing the students’ self-efficacy on conducting a science research project. The captured dynamics will provide us a theory and model with a panoramic view of handling the future classes in conducting a science investigatory project in all science research curriculums.